Sphingomonas paucimobilis endophthalmitis postpenetration ocular trauma: a rare case report - Alias, Nur Syifa Athirah Qistina; Abd Bari, Muhd. Syafi; Jabbari, Aidila Jesmin (OMAN MEDICAL SPECIALTY BOARD, 2023)
Endophthalmitis is an uncommon purulent inflammation of the intraocular fluids secondary to endogenous or exogenous causes. It is known that posttraumatic endophthalmitis had a notably poor visual outcome, and it poses therapeutic challenges. Therefore, early organism detection would be beneficial in therapeutic management and are able to reduce long-term complications. This case report describes a patient with a rare positive culture-proven Sphingomonas paucimobilis endophthalmitis due to penetrating ocular trauma by a metal brush over the right eye. A 36-year-old man presented with progressively worsening right eye redness and blurring of vision with pain for 3 days following ocular penetration by a metal brush during grinding. On initial presentation, his visual acuity was 6/12 over the right eye and 6/6 over the left eye. His visual acuity deteriorated to hand movement 5 days later with worsening of ocular infection over the right eye despite topical and oral antibiotics. B-scan revealed dense vitreous infiltration. A vitreous tap was done, and a combination of intravitreal vancomycin and ceftazidime was administered. Vitreous culture isolated Gram negative S. paucimobilis. The patient was planned for early vitrectomy; however, the patient opted for conservative treatment. Therefore, the patient received intravitreal vancomycin and intravitreal ceftazidime injections every 48–72 h. Published articles on S. paucimobilis endophthalmitis postocular penetration are extremely limited. This case report may provide a better understanding of the presentation and is able to aid with early diagnosis and treatment initiation for future reference.